Regioselective synthesis of chiral dimethyl-bis(ethylenedithio)tetrathiafulvalene sulfones - Pop, Flavia; Avarvari, Narcis (Beilstein Journal of Organic Chemistry, 2015)
Enantiopure (R,R) and (S,S)-dimethyl-bis(ethylenedithio)tetrathiafulvalene monosulfones have been synthesized by the aerial oxidation of the chiral dithiolates generated from the propionitrile-protected precursors. Both enantiomers crystallize in the orthorhombic chiral space group P212121. They show a boat-type conformation of the TTF moiety, a rather rigid dithiin sulfone ring and the methyl groups in a bisequatorial conformation. Cyclic voltammetry measurements indicate fully reversible oxidation in radical cation and dication species.
Keywords: chirality; crystal structures; molecular materials; sulfones; tetrathiafulvalenes